Non-Volumetric Pricing is a Threat to Water Reserves - Hafiz Usama Imad; Muhammad Akram Akhund; Muhammad Ali; Ashfaque Ahmed Pathan; Aftab Ahmed (Salehan Institute of Higher Education, 2019)
Pakistan is a country having the world largest irrigation system but despite that, it is facing several droughts and floods. The storage capacity of the country is only 30 days whereas the required standard capacity is 120 days. The major source of water for the country is surface water and in many areas, groundwater is also used in a large quantity for domestic as well as agricultural use. Pakistan has large water reservoirs but still, it is facing serious challenges in providing safe drinking water due to the mismanagement of natural water resources. The major cause behind the depletion of water resources of the country is over-use of water. The main objective of this study is to find the behavior of people by comparing volumetric and nonvolumetric water use and the price they pay for both. There is a need to compare volumetric and nonvolumetric water pricing scenarios and its impact on water conservation for the district of Hyderabad. The study was conducted through questionnaire surveys, from three administrative units of the Hyderabad namely Qasimabad, Latifabad, and City. Three types of water utilities, namely Tapped water (water supplied by WASA), groundwater and tankered water were found as major sources for domestic use. The domestic use of groundwater is found to be mostly unpaid, while people having lined water services pay an average of Rs 300 (USD 2.2) but the percentage of these people is only 60%. On the other hand, people who consume tankered water (volumetric based charging) are paying on average Rs 5000 (USD 35.7) per month. The main finding of this study is that the households which were using tanker water were more careful in optimizing the use of water as compared to those who were using tapped water. Therefore, considering the economic worth of water, if it is charged on a volumetric basis then the misuse of water can be reduced noticeably.